Electrochemical degradation of surfactants in domestic wastewater using a DiaClean® cell equipped with a boron-doped diamond electrode - Cisneros-León, Dayana G.; Espinoza-Montero, Patricio J.; Bolaños-Mendez, Diego; Alvarez-Paguay, Jocelyne; Fernández, Lenys; Saavedra-Alulema, Pablo F.; Lopez, Kelly; Astorga, Diana; Piñeiros, José Luis (Frontiers in Chemistry, 2023)
Although some traditional water treatment processes have been proposed for domestic and industrial water reclamation, these are often inadequate, ineffective, or expensive. Within this context, electrochemical technologies have become a promising tool for the treatment of wastewater contaminated by organic pollutants as surfactants. This work carried out the electrochemical degradation of surfactants present in domestic wastewater, using a DiaClean® cell, in a recirculation system, equipped with a boron-doped diamond (BDD) anode and stainless-steel as cathode. The effect of the flow rate (flow = 1.5, 4.0, 7.0 L min-1) and current density (j = 7, 14, 20, 30, 40, 50 mA cm-2) was studied. The degradation was followed by the concentration of surfactants, chemical oxygen demand (COD), and turbidity, also pH value, conductivity, and temperature were evaluated. Finally, the mineralization was followed by total organic carbon (TOC) under optimal operating conditions. The results showed that the best conditions for the efficient mineralization of wastewater were applying j = 50 mA cm2 and a flow rate of 1.5 L min-1 during 6 hours of electrolysis, achieving removal of 89.7% of surfactants, 90.7% of COD, 89.4% of turbidity, and 94.0% of mineralization analyzed by the removal of TOC. The kinetic constant demonstrated that the electrochemical process adjusted to a pseudo-first order kinetic reaction. Finally, the energy consumption was analyzed and the operating cost of 80.0 USD m-3 was calculated. Therefore, this technology is proposed as a promising alternative for the efficient mineralization of surfactants and organic compounds present in domestic wastewater.